Study of Terpenoid Synthesis and Prenyltransferase in Roots of Rehmannia glutinosa Based on iTRAQ Quantitative Proteomics - Chen, Peilei; Wei, Xiaoyan; Qi, Qianting; Jia, Wenjing; Zhao, Mingwei; Wang, Huina; Zhou, Yanqing; Duan, Hongying (Frontiers in Plant Science, 2021)
Rehmannia glutinosa has important medicinal value, terpenoid is one of the main active components in R. glutinosa. In this study, iTRAQ technique was used to analyze the relative abundance of proteins in roots of R. glutinosa, and 6752 reliable proteins were quantified. GO enrichment results indicated that most proteins were involved in metabolic process or cellular process, 57.63% proteins had catalytic activity, and 65.80% proteins were enriched in membrane-bounded organelle. In roots of R. glutinosa, there were 38 KEGG enrichments with significance, more DEPs were found in some pathways, especially the pathway of proteasome and TCA cycle with 15.0% DEPs between elongation stage and expansion stage of roots. Furthermore, 5 KEGG pathways of Terpenoid synthesis were found, most of prenyltransferases belong to FPP/GGPP synthase family, involved in terpenoid backbone biosynthesis and all interacted with biotin carboxylase CAC2. Compared with that at elongation stage, many prenyltransferases exhibited higher expression at expansion stage or maturation stage of roots. In addition, eight FPP/GGPP synthase encoding genes were cloned from R. glutinosa, such as FPPS, FPPS1, GGPS, GGPS3, GGPS4, GGPS5, GPPS and GPPS2, introns were also found in FPPS, FPPS1, GGPS5 and GGPS2, and FPP/GPP synthases were more conservative in organisms, especially in viridiplantae, in which the co-ocurrence of GPPS or GPPS2 was significantly higher in plants. Further analysis found that FPP/GGPP synthases of R. glutinosa were divided into three kinds, GGPS, GPPS and FPPS, and their gene expression was significantly diverse in different varieties, growth periods or tissues of R. glutinosa, compared with that of GGPS, the expression of GPPS and FPPS was very higher in R. glutinosa, especially at expansion stage and maturation stage. Thus, the synthesis of terpenoids in roots of R. glutinosa is intricately regulated and need to be further studied.